Investigation of the High-Resolution Fourier Spectrum of the ν3+ν4 Band of the 13CH3D Molecule - Beryozkin K. B. Kirill Borisovich; Fomchenko A. L. Anna Leonidovna; Leroy K. A. Klod (Claude) Andre; Bauerecker (Bauerekker) Z. (S.) H. Zigurd (Sigurd) Hermann; Bekhtereva E. S. Elena Sergeevna; Khorneman V. M. Veli-Matti (2017, 2017)
Title screen